Characterization and Photocatalytic Activity of Nanoparticulate LuVO4 Prepared by Sol-Gel Method. Issue 206 (23rd March 2020) - Pan, Bingqi; Tang, Peisong; Gao, Shanshan; Shen, Weibin; Chen, Haifeng
Abstract: Using lutetium oxide, nitric acid, ammonium vanadate and citric acid as main materials, LuVO4 was prepared by a facile sol-gel method. The gel of LuVO4 was kept at 100 °C for 24 h to get the xerogel. Then, the xerogel was, respectively, calcined in muffle furnace at 500 °C, 600 °C, 700 °C and 800 °C to make single phase nanoparticulate LuVO4 . The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), Fourier transform infrared (FT-IR) spectroscopy and diffuse reflectance spectroscopy (DRS). The results showed that the pure LuVO4 can be obtained through calcination at 700–800 °C. LuVO4 had an average particle size of 100 nm and the band gap was 2.25 eV. The photocatalytic activities of LuVO4 were investigated by methylene blue which was used as simulated sewage. Under visible light, LuVO4 showed good photocatalytic degradation activity for degradation of methylene blue. This indicated that LuVO4 has broad practical application prospects in the field of photocatalytic degradation of organic pollutants.